EFFISIENSI PENGGUNAAN ALAT TANGKAP BUBU (Trap) YANG BERBEDA TERHADAP PENDAPATAN NELAYAN RAJUNGAN (Portunus pelagicus)DI DESA KEMANTREN KECAMATAN PACIRAN KABUPATEN LAMONGAN JAWA TIMUR - HARTINI, SUZANA SRI; SUMARYAM, SUMARYAM (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2018)
ABSTRACTTypes of fishing gear operating in a waters, so there are really many types of fishing gear and techniques used. However, many of these fishing gear have many similarities in operation even though some are simpler and some are more complex. The study was conducted to identify trap equipment which included fishing gear specifications, how to operate fishing gear and catches using basic fishing traps and floating traps at various fishing locations and analyze differences in income in the Kemantren Village of Paciran Subdistrict, Lamongan Regency. From the calculation results there are differences in income between the two groups of crab fishing business, the income of basic bubu fishing gear is Rp. 341,068,663 per year and floating bubu fishing gear is Rp. 179,141,330 per year, with business finances obtained the value of B / C ratio. the base is 5.2 and the B / C ratio of the floating bubu catcher is 4.8, thus indicating the basic bubu trap is more efficient than the floating trap.Â Â Keyword: Rajungan (Portunus pelagicus), alat tangkap bubu dasar , alat tangkap bubu apung, B/C Ratio